Robotic Surgery in Pakistan: Precision, Progress, and Challenges - Kanza Mehmood; Aakash Kumar (Journal of Bahria University Medical and Dental College, 2023)
The Da Vinci Surgical (DVS) system, an example of surgery has made significant advancements since its introduction, in 2000. Thanks to state of the art technology surgeons are now able to perform procedures with exceptional precision and minimal invasiveness. These include urological, thoracic and cardiac surgeries, which have revolutionized the field of surgery.